Konsep Statistik dan Jenis-Jenisnya - Aisyah Amalia; Ayu Nurani; Zulpan; Ahmad Husein (Journal of Literature Review, 2025)
This study discusses the fundamental concepts and types of statistics  that play a crucial role in data processing and analysis. In the digital era, statistics serve as primary tool for data-based decision-making acroos various fields such as education, economis, health, and industry. The purpose of this research is to explain the definition of statistics, its classifications, and its applications in daily life. This study employs a descriptive qualitative appoarch using library research by analyzing various sources such as books, journals, and previous studies. The findings indicate that statistics are divided into two main categories, descriptive statistics, which describe data as it is, and infererntial statistics, which draw conclusions about a population based on sample data. Inferensial statistics include parametric and nonparametric analyses, distinguished by their distributionsl assumptions. Furthermore, statistics have broad applications in health, economics, industry, business, and scientific research. Overall, this study emphasizes that a solid understanding of statistics is essential for data analysis and evidence- based, rational decision-making.